The Twisted Personality Development as Reflected in Stephen King’s Carrie Novel - Helmita, Helmita; Rezky Mahesa, Salsabila (Jurnal Ilmiah Pendidikan Scholastic, 2024)
The character of Carrie and the elements that shape her character are the primary foci of the thesis. Carl Jung's theory of personality, which delves into archetypes like Persona and Shadow, is utilized in this thesis to get insight into Carrie's mind. This study makes use of a descriptive and qualitative approach. The research shows that Carrie's devout mother and her classmates, who treat her badly and reject her often, have a significant impact on her personality. Then, her character quirks start to take shape and become apparent. 1) Carrie is calm and careful around her friends, and she follows her mother's orders to the letter. She exudes all of these qualities in her manner. Character traits are shaped by the influences of one's immediate social circle and the environment in which one grows up. 2) Carrie's shadow is defined by defiance, rage, retaliation, bodily harm, and acts of violence. Shadow arises from her insecurities and the overwhelming presence of bullies and ridicule, which prevent her from appreciating her own great characteristics. Both of these phases in Carrie's life have been caused by her immense desire to transform her life into the life she wishes it could be. Whenever Carrie fails to achieve her lifelong objective, her self-esteem starts to deteriorate.